Odpowiedź :
Odpowiedź:
a) x/3 +1 = 5/6 +x/2 /*6
2x+6 =5 + 3x
2x-3x= 5-6
-x= - 1 /*(-1)
x=1
spr.. 1/3 + 1= 5/6 +1/2
1 i 1/3= 5/6+ 3/6
1 i 1/3= 8/6
1 i 1/3= 1 i 2/6 = 1 i 1/3
L=P
b) 2x-3 /4= 1/2 +x /*4
2x-3 = 2 +4x
2x-4x= 2+3
-2x= 5 /: (-2)
x= - 5/2= - 2 i 1/2
spr... 2*(-5/2) -3 /4= 1/2 + (-5/2) -4/2
-5-3/ 4= - 4/2
-8/4= - 2
-2=-2
L=P
c) x+2 /9 +x-1 /3= 1 /*9
x +2 +3x -3= 9
4x= 9 +3-2
4x= 10 /:4
x= 10/4= 2 i 1/2
spr... 10/4 +2 /9 +10/4 -1 /3=1
2 i 1/2 +2 :9 + 10/4-1 :3= 1
9/2 *1/9 + 1 i 1/2 *1/3=1 ( skracamy 9 i 9 przez 9)
1/2 + 3/2*1/3= 1 ( skracamy 3 i 3 przez 3)
1/2 +1/2=1
1=1
d) 2x+3 /5 = 2-x /3 +x *15
6x +9= 10 -5x +1 5x
6x+5x-15x= 10-9
-4x= 1 /*(-1)
4x= - 1 /:4
x= - 1/4
spr. 6*(-1/4) +9= 10 + 10*(-1/4)
-6/4 +9= 10- 10/4
- 1 i 1/2 +9= 10- 2 i 1/2
7 i 1/2= 7 i 1/2
L=P
L=P
Szczegółowe wyjaśnienie: